Industrial‐Level CO2 Electroreduction Using Solid‐Electrolyte Devices Enabled by High‐Loading Nickel Atomic Site Catalysts. Issue 31 (29th June 2022) - Wang, Shuguang; Qian, Zhengyi; Huang, Qizheng; Tan, Yingjun; Lv, Fan; Zeng, Lingyou; Shang, Changshuai; Wang, Kai; Wang, Guoqing; Mao, Yandong; Wang, Yan; Zhang, Qinghua; et al.
Abstract: Transition‐metal atomic site catalysts (ASCs) are a new class of catalytic system for CO2 electroreduction, however, their practical application is greatly hindered by the challenge that it's still difficult for them to simultaneously achieve industrial‐level current density and high selectivity. Herein a new strategy is reported for hundreds of gram‐scale and low‐cost production of Ni‐ASCs on 3D porous nanocarbon with high‐loading NiN3 sites for greatly boosting the electroreduction of CO2 to CO with both industrial‐level current density and high selectivity. It is discovered that although Ni‐ASCs with high‐loading (Ni‐ASCs/4.3 wt.%) and low‐loading (Ni‐ASCs/0.8 wt.%) both show above 95% Faradic efficiency for CO (FECO ) under a wide potential range in H‐cell, in flow cell, Ni‐ASCs/0.8 wt.% can only achieve FECO of 43.6% at a current density of 343.9 mA cm −2, significantly lower than those (95.1%, 533.3 mA cm −2 ) of Ni‐ASCs/4.3 wt.% under same potential, first revealing the important role of high‐loadings of single atom sites in promoting the high‐selectivity electrolysis at industrial‐level current density. Most importantly, it is demonstrated that Ni‐ASCs/4.3 wt.%‐based membrane electrode assembly (MEA) exhibits outstanding durability at industrial‐level current density of 360.0 mA cm −2, which is one of the best performances for the realistic electroreduction of CO2 to CO in the reported ASCs‐based MEA systems. Abstract : A new strategy for hundreds of gram‐scale and low‐cost production of Ni‐atomic site catalysts (ASCs) is reported. It is discovered that Ni‐ASCs/4.3 wt.% can achieve high FECO (95.1%) at current density of 533.3 mA cm −2, significantly higher than that (43.6%, 343.9 mA cm −2 ) of Ni‐ASCs/0.8 wt.% under same potential, indicating the important role of the high‐loading of metal atom sites in promoting high‐selectivity electrolysis at industrial‐level current density.